CLUBB as a unified cloud parameterization: Opportunities and challenges. Issue 11 (1st June 2015) - Guo, H.; Golaz, J.‐C.; Donner, L. J.; Wyman, B.; Zhao, M.; Ginoux, P.
Abstract CLUBB (Cloud Layers Unified by Binormals) is a higher‐order closure (HOC) method with an assumed joint probability density function (PDF) for the subgrid variations in vertical velocity, temperature, and moisture. CLUBB has been implemented in the atmospheric component (AM3) of the Geophysical Fluid Dynamics Laboratory general circulation model AM3‐CLUBB and successfully unifies the treatment of shallow convection, resolved clouds, and planetary boundary layer (PBL). In this study, we further explore the possibility for CLUBB to unify the deep convection in a new configuration referred as AM3‐CLUBB+. AM3‐CLUBB+ simulations with prescribed sea surface temperature are discussed. Cloud, radiation, and precipitation fields compare favorably with observations and reanalyses. AM3‐CLUBB+ successfully captures the transition from stratocumulus to deep convection and the modulated response of liquid water path to aerosols. Simulations of tropical variability and the Madden‐Julian oscillation (MJO) are also improved. Deficiencies include excessive tropical water vapor and insufficient ice clouds in the midlatitudes.